Legalitas Penggunaan Sidik Jari Elektronik dan Tanda Tangan Elektronik Terkait Keabsahan Akta Notaris - Sisthayoni, Anak Agung Ayu; Wisanjaya, I Gede Pasek Eka (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 03 (2022)DO - 10.24843/AC.2022.v07.i03.p8, 2022)
The purpose of this study is to determine the arrangement of fingerprints and electronic signatures in the creation of a notary deed as well as the legality of the fingerprint and electronic signature in relation to the notary deed's validity. In order to address the issue of ambiguity in norms, this research used a normative legal research methodology based on primary, secondary, and tertiary legal sources that were obtained through document study techniques and examined using content analysis techniques and argumentative tactics. The research in this paper shows that the use of fingerprints and electronic signatures on the minutes of notary deeds is not specifically regulated by the laws and regulations nowadays. As a result, the application of fingerprints and electronic signatures is unclear and their legality is put into question, which will affect the authenticity of the notary deed. Authentic deeds cannot be made in electronic form and cannot be taken into consideration as legal evidence, according to Article 5 Paragraph 4 of Law Number 11 of 2008 concerning Electronic Information and Transactions.